Fragmented Landscapes and Planscapes—The Double Pressure of Increasing Natural Resource Exploitation on Indigenous Sámi Lands in Northern Sweden - Carl Österlin; Kaisa Raitio (Resources, 2020)
Human induced land-use change through natural resource extraction has significant ecological, social and cultural effects for indigenous communities. Indigenous rights, cultural practices and identities are strongly interconnected with traditional lands. In northern Sweden, the cumulative effects from natural resource extraction have become increasingly problematic for Sámi reindeer herding. Land use planning and permit processes are organized based on single projects or policy sectors, instead of the needs and rights involving reindeer herding. Existing research has demonstrated loss of ground and arboreal lichen, fragmentation of pastures and reindeer avoidance of otherwise valuable pastures due to disturbance caused by competing land uses. There is however a lack of synthesis of the amount and scale of encroachments on traditional Sámi territories in Sweden so far. Likewise, while research has looked at weaknesses of the sectoral regulations in terms of cumulative impact assessment and the inadequate recognition of Sámi reindeer herding rights, no studies have analyzed the meta-pressure caused by the fragmented planning regime as a whole, as the amount of regulations regarding different land use sectors and permitting processes increases with each new type of competing activity. Through the concept of double pressure caused by the inter-related processes of fragmented landscapes and fragmented ‘planscapes’, this study seeks to capture the actual pressure the affected communities are currently experiencing. Using multiple quantitative and qualitative data sets consisting of Geographical Information Systems, policy documents, workshops discussions and interviews, we study how natural resource extraction like mining and wind energy has increased on traditional indigenous Sámi lands in northern Sweden. By expanding the analytical focus from today’s landscapes to both planscapes and the pressure from not-yet realized future projects, our results highlight the need for a holistic understanding of the situation ...